Application of Remote Sensing Technique in the Enumeration of Sandal Trees - Sen-Sarma, P. K.; Ananthanarayana, A. K.; Pabthasarathi, K. (Indian Forester, 1978)
The enumeration of sandal is presently being done by the conventional ground survey method which is time consuming and becomes difficult if sandal is located in not easily accessible areas like valley, hills etc. The feasibility of the application of Remote Sensing Technique for sandal enumeration was, therefore, studied. It has been found that aerial photography is feasible for a rapid but at the same time fairly accurate enumeration of the sandal trees in forest areaS.